Additions to the catalogues of type and figured fossil cephalopoda in the British Museum (Natural History) - Phillips, D. (Trustees of the British Museum, 1987)
This is the final part of a series of catalogues listing the type of fossil cephalopoda in the British Museum (Natural History). Amended records and records omitted from the previous volumes are included here, together with additional records up to the end of June 1986.